Comparison on Isolation Technique of Vaninilin from Vanili Fruit (Vanilla planifolia Andrews - Haryadi, Winarto; Handayani, Sri; Arianingrum, Retno (EKSAKTA: Journal of Sciences and Data Analysis, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Isolation of vanilin from vanili fruit by two method; maseration and Soxhlet using ethylacetate, ethanol and chloroform solvents has been investigated. Extraction result was hydrolized using sodium hydroxide by acidification using chloride acid. Filtrate was extracted by using chloroform and the targeted vanilin was separated by evaporation. Putrification was enganged by rechrystallization using aquadest-ethanol. Elucidation to the compound structure was performed by FTIR spectrophotometer, H-NMR, C-NMR, HMQC and HMBC. It is noted that vanilin isolation by soxhletazion procedure was more effective compared to maseration. Ethylacetate was more effective solvent than chloroform and conversely ethanol is inefective for the isolation. Keywords: vanilin isolation, soxhlet isolation, maseration